1990
DOI: 10.1017/s002221510015858x
|View full text |Cite
|
Sign up to set email alerts
|

Long distance travel by children for tonsillectomy: experience of the ORL department at Princess Alexandra Hospital (PAH), Royal Air Force, Wroughton, Swindon

Abstract: An audit was carried out to assess the acceptability of long distance travel for elective tonsillectomy and adenoidectomy. Seventy nine children travelled 70 miles with their father or mother to P. A. H. from Mid Glamorgan where the E.N.T. waiting list delay for tonsillectomy was some two years.Most of the families who were offered the travel arrangements agreed and from the results of the questionnaires answered by the first 50 families, it was shown to be a successful exercise as both the children and parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In our previous article, 11 2 other studies of follow-up telephone surveys were cited. 17,18 The first evaluated transportation, accommodations, and meals provided for 50 patients and their families who traveled long distances for surgery. The second study examined the pain and hydration status of 52 patients on the first day after surgery and 14 days after surgery, and concluded that caregivers were able to handle mild dehydration symptoms and postoperative pain at home.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous article, 11 2 other studies of follow-up telephone surveys were cited. 17,18 The first evaluated transportation, accommodations, and meals provided for 50 patients and their families who traveled long distances for surgery. The second study examined the pain and hydration status of 52 patients on the first day after surgery and 14 days after surgery, and concluded that caregivers were able to handle mild dehydration symptoms and postoperative pain at home.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also found that 30% of these patients had consulted a health care provider during the postoperative period. 17,18 More recently, Valtonen et al 19 studied patient contact with health care professionals after elective tonsillectomy and found that 43.8% of patient-initiated contact with health care professionals was most often related to pain or hemorrhage, and information given over the telephone was sufficient in nearly half the cases. A study among patients with cataracts compared the efficacy of evaluations the day after surgery performed in the hospital, at home, and over the telephone.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis could not be tested in our study and the finding may not apply to waiting times, which are longer than in this study. In two English studies, the uncertainty about the waiting time at the local hospital was greater, and the patients were more likely to accept to travel much farther, suggesting that uncertainty was important to patients' choice [8,9]. However, studies of patients' views on waiting time for surgery indicate that the numerical length of waiting time indeed influences patients' satisfaction negatively: cataract patients generally accept waiting times of 3 months or less, while waiting times of 6 months or more are likely to be perceived as too long [10,11].…”
Section: Waiting Timementioning
confidence: 99%
“…Other Danish counties have carried out similar initiatives, but we have not found any scientific studies of these projects. Two English studies presented different patient groups with a simple trade-off between a long waiting time and a long distance to hospital and found very different results: roughly half of patients waiting for surgery chose re-referral to a distant hospital [8], while 95% of parents of clinically relevant children with recurrent tonsillitis chose a distant hospital [9]. New legislation allows Danish patients to choose among a larger number of public and private hospitals, and hospitals' financial incentives to receive patients have been strengthened, making it more difficult to perform a prospective study of a simple trade-off between short distance and short waiting time.…”
Section: Introductionmentioning
confidence: 99%
“…Two other telephone follow-up studies were identified in the literature. 18,19 The first evaluated transportation, accommodations, and meals provided for 50 patients and their families who traveled long distances for surgery. The authors did not comment on specific complications.…”
Section: Commentmentioning
confidence: 99%